Library patrons' privacy : questions and answers - Valenti, Sandra J.; Lund, Brady, 1994-; Beckstrom, Matthew (Libraries Unlimited, 2022)
"A great resource for busy library professionals to keep up with the patron privacy crises and questions they frequently face. This book synthesizes librarian opinions, library policies, case studies, empirical research for library and information science and other fields, American Library Association publications, and privacy philosophy"--